Sowing the Seeds of Health: Training of Community Health Advisors to Promote Breast and Cervical Cancer Screening among Latina Immigrants in Alabama (2016)
ABSTRACT: Latinas in the U.S. are disproportionately affected by breast and cervical cancer. This project sought to develop and evaluate a culturally relevant training for Community Health Advisors (CHA) to promote breast and cervical cancer screening among Latina immigrants in Alabama. The Empowerment Model guided training development and implementation supported by a formative evaluation and a Community Advisory Committee. The 16-hour CHA training included two intertwined components: knowledge and skills. Fifty-six (56) Latinas participated in the CHA training in six Alabama counties. The training increased the CHAs’ (1) knowledge of cancer screening and other health topics and (2) their perceived confidence to communicate with women in their communities about cancer screening and to motivate them to attain cancer screenings. This work demonstrates the application of a transformative philosophical framework to promote capacity-building among CHAs toward the development and implementation of strategies to promote breast and cervical cancer screening among Latina immigrants.